The effect of timing of emergency cholecystectomy for acute cholecystitis on peri-operative outcomes: A national registry-based study - Kehoe, John David; O'Connell, Robert; Linehan, Eimear; Hardy, Niall; Creavin, Ben; Gall, Tamara; McEntee, Gerry; Conneely, John (The surgeon (Edinburgh), 2025)
A selection of international guidelines suggest that emergency cholecystectomy within 72 h of admission is the treatment of choice for acute cholecystitis. The aim of this study was to analyse the interval from presentation to operative intervention for acute cholecystitis in Ireland and its impact on peri-operative outcomes. This was a national retrospective observational study of all patients that underwent an emergency cholecystectomy for acute cholecystitis in Ireland between January 2017 and July 2023. Data collected included: demographics, co-morbidities, length of stay, operative approach, post-operative interventions, in-patient mortality, and readmissions. Subjects were stratified based on time from presentation to theatre and outcomes were compared between groups. 3585 patients underwent an emergency cholecystectomy for acute cholecystitis–2005(55.9 %) within 72 h of admission, 1072(29.9 %) within 72 hours-7 days, 416(11.6 %) within 8–14 days and 92(2.6 %) beyond 14 days. Earlier progression to theatre was predicted by female sex (X2(3) = 10.402,p = 0.015), less co-morbidities (X2(12) = 95.723,p=<0.001), and younger age (H(3) = 92.591,p=<0.001). On logistic regression, age >65(OR 1.565,p < 0.001), male sex(OR 1.348,p = 0.002), increasing co-morbidities(OR 1.586,p = 0.009) and increased “time to theatre”(72hrs-7days(OR 1.616,p < 0.001), 8–14days(OR 3.84,p < 0.001), >14days(OR 5.929,p < 0.001)) were risk factors for a composite of adverse outcomes (mortality, 30-day readmission, post-operative ERCP/IR drain, conversion to open, CBD injury). Subgroup analysis of the <72 h group displayed no difference in outcome. Despite international guidance, just over half of emergency cholecystectomies for acute cholecystitis are performed within 72 h in Ireland. Prolonging “time to theatre” is associated with a stepwise deterioration in outcomes across a wide variety of measures. •Cholecystectomy within 72 h is the optimal treatment for acute cholecystitis.•We analysed all emergency cholecystectomies performed in Ireland over 7 years.•Only 55.9 % of the 3585 cholecystectomies were performed within 72 h of admission.•Younger, female and less co-morbid patients are more likely to be operated on earlier.•Prolonged “time to theatre” increases the risk of negative outcomes.